Development of Nanoporous Ni-Sn Alloy and Application for Chemoselective Hydrogenation of Furfural to Furfuryl Alcohol - Rodiansono Rodiansono; Takayoshi Hara; Nobuyuki Ichikuni; Shogo Shimazu (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
A very simple synthetic procedure was developed for the preparation of Ni-Sn alloy catalysts that were utilised for chemoselective hydrogenation of furfural, producing furfuryl alcohol almost exclusively. The mixture of nickel nanoparticles supported on aluminium hydroxide (R-Ni/AlOH) and a solution containing tin was treated under hydrothermal condition, producing the as prepared nickel-tin alloy supported on aluminium hydroxide (Ni-Sn/AlOH). H2 treatment at range of temperature of 673-873 K for 1.5 h to the as prepared Ni-Sn/AlOH produced nanoporous Ni-Sn alloy catalysts. XRD patterns and SEM images revealed that the formation of Ni-Sn alloy of Ni3Sn and Ni3Sn2 phases and the transformation of crystalline gibbsite and bayerite into amorphous alumina were clearly observed after H2 treatment at 873 K. The formation of the Ni-Sn alloy may have played a key role in the enhancement of the chemoselectivity. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)